Term Structure Multiplicity and Clientele in Markets with Transactions Costs and Taxes - Dermody, Jaime Cuevas; Prisman, Eliezer Zeev (Journal of Finance, 1988)
The authors investigate term structure with realistic transactions costs and taxes. Its properties are derived from a certain no-arbitrage condition via duality theory in convex programming. Transactions costs imply an infinite multiplicity of term structures. A simple example with realistic transactions costs shows that this multiplicity can induce a valuation range of over 277 basis points. Transactions costs also allow equilibrium without short sale restrictions. The authors find the minimum transactions costs that prevent arbitrage. In addition, the exact conditions for weak clientele, in which investors will not buy some bonds and may not sell any that they already hold, are established.